1992
DOI: 10.1007/bf01957719
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capacity of subjects exposed to methimazole or propylthiouracil in utero

Abstract: Antithyroid drugs, considered the treatment of choice for hyperthyroidism during pregnancy, may have an adverse effect on intellectual development of the offspring. We examined the intellectual capacity of 31 subjects aged 4-23 years, born to women with Graves disease who received antithyroid drugs throughout pregnancy. Methimazole 40-140 mg/week (n = 15) or propylthiouracil 250-1400 mg/week (n = 16) was given. I.Q. was assessed using the Wechsler test appropriate for age. Twenty-five unexposed siblings served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…No differences in total IQ and verbal and performance skills were found in 31 patients aged 4 to 23 years (median age 11 years) born to mothers with GD, compared with 25 controls; all patients were euthyroid at birth. 20 Similar results were found in 2 other studies. 21,22 In contrast, in 8 children with neonatal hyperthyroidism, craniosynostosis was identified in 6 and intelligence tests were below average in 4 at ages 2 years or older.…”
Section: Introductionsupporting
confidence: 88%
“…No differences in total IQ and verbal and performance skills were found in 31 patients aged 4 to 23 years (median age 11 years) born to mothers with GD, compared with 25 controls; all patients were euthyroid at birth. 20 Similar results were found in 2 other studies. 21,22 In contrast, in 8 children with neonatal hyperthyroidism, craniosynostosis was identified in 6 and intelligence tests were below average in 4 at ages 2 years or older.…”
Section: Introductionsupporting
confidence: 88%
“…Two studies have shown no differences in thyroid function or physical and psychomotor development between children born to CBZ/MMI or PTU treated hyperthyroid mothers during pregnancy and those born to euthyroid mothers [61,62]. However, these studies were small and underpowered to detect even substantial differences.…”
Section: Resultsmentioning
confidence: 99%
“…Effect on pediatric physical and mental growth No differences in thyroid function or physical and psychomotor development has been found between children born to MMI-or PTU-treated hyperthyroid mothers during pregnancy and those born to euthyroid mothers (43,44).…”
Section: What Are the Associated Complications With Antithyroid Drugsmentioning
confidence: 98%